Analysis of tweets about football: 2013 and 2018 leagues in Turkey. Issue 9 (2nd September 2019) - Ozturkcan, Selcen; Kasap, Nihat; Tanaltay, Altug; Ozdinc, Mesut
ABSTRACT: Football has recently developed into a unique sector with complex management and marketing functions, where novel communication technologies are employed. In this paper, we aim to contribute to the numerous fields involving emerging European sports marketing literature, social media analytics, and digital consumer behaviour. Our purpose is to explore Twitter use related with football by analysing real-time streamed data in offering a longitudinal perspective by focusing on 2013 and 2018 leagues in Turkey via the use of social media analytics framework. Retrieved dataset involved randomly selected publicly available 370 thousand and 6.8 million real-time tweets in 2013 and 2018 leagues, respectively. We report that majority of tweets about the football was posted within the three-hour window before the match independent of the match result and the importance of the result. Moreover, pre-match tweeting volume was almost a crystal ball signalling match winning. Our findings are valuable for sports managers and marketers where some key suggestions provided are to involve particular contexts of winning or losing in their after-match marketing plans, to value weekdays as much as the weekends, and to utilise the after-work prime time of social media engagement.